Mutant characterization and in vivo conditional repression identify aromatic amino acid biosynthesis to be essential for Aspergillus fumigatus virulence - Sasse, Anna; Hamer, Stefanie N.; Amich, Jorge; Binder, Jasmin; Krappmann, Sven (Virulence, 2016)
Pathogenicity of the saprobe Aspergillus fumigatus strictly depends on nutrient acquisition during infection, as fungal growth determines colonisation and invasion of a susceptible host. Primary metabolism has to be considered as a valid target for antimycotic therapy, based on the fact that several fungal anabolic pathways are not conserved in higher eukaryotes. To test whether fungal proliferation during invasive aspergillosis relies on endogenous biosynthesis of aromatic amino acids, defined auxotrophic mutants of A. fumigatus were generated and assessed for their infectious capacities in neutropenic mice and found to be strongly attenuated in virulence. Moreover, essentiality of the complete biosynthetic pathway could be demonstrated, corroborated by conditional gene expression in infected animals and inhibitor studies. This brief report not only validates the aromatic amino acid biosynthesis pathway of A. fumigatus to be a promising antifungal target but furthermore demonstrates feasibility of conditional gene expression in a murine infection model of aspergillosis.
EVALuna2:7691